A cautionary tale regarding 'believing' allegations of historical child abuse. Issue 1 (2nd January 2017) - Smith, Mark
ABSTRACT: Allegations of sexual abuse made against the former BBC entertainer, Jimmy Savile by former pupils of a girls' residential school attracted worldwide publicity when they were reported in a TV programme in 2012. The Savile case has had major political and cultural reverberations, with the establishment of official inquiries across the countries of the UK to investigate claims of historical abuse. Responses reinforce what has become a default position in respect of allegations of historical abuse—that we should believe those telling such stories. This article presents a case study, which introduces some caution in that regard. Accounts of the past are constructed in particular social and cultural contexts and cannot be regarded as necessarily reflecting any wider, objective reality. Moreover, unquestioning 'belief', while it may be posited as giving voice to former care home residents, may mask another politics of voice, within which these views are appropriated by more powerful cultural elites. This situation has implications for those who claim abuse, those accused of such abuse and for natural and social justice. The article begins to address some of the ethical issues raised when professionals encounter stories of historical abuse.